2014
DOI: 10.1103/physreva.90.032106
|View full text |Cite
|
Sign up to set email alerts
|

Quantum decoherence of an anharmonic oscillator monitored by a Bose-Einstein condensate

Abstract: The dynamics of a quantum anharmonic oscillator whose position is monitored by a Bose-Einstein condensate (BEC) trapped in a symmetric double well potential is studied. The (non-exponential) decoherence induced on the oscillator by the measuring device is analysed. A detailed quasiclassical and quantum analysis is presented. In the first case, for an arbitrary initial coherent state, two different decoherence regimes are observed: An initial Gaussian decay followed by a power law decay for longer times. The ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The atoms of the condensate are confined in a double well and can tunnel from one side of the potential to another, depending on the position of the oscillator. As shown by Alonso et al (2014) and Brouard et al (2011), if one considers the condensate as an envi- FIG. 1 (a) The experimental set-up consists of a laser, which is split into a signal beam and a local oscillator (LO).…”
Section: A Non-markovian Effects In Different Scenariosmentioning
confidence: 99%
“…The atoms of the condensate are confined in a double well and can tunnel from one side of the potential to another, depending on the position of the oscillator. As shown by Alonso et al (2014) and Brouard et al (2011), if one considers the condensate as an envi- FIG. 1 (a) The experimental set-up consists of a laser, which is split into a signal beam and a local oscillator (LO).…”
Section: A Non-markovian Effects In Different Scenariosmentioning
confidence: 99%
“…The atoms of the condensate are confined in a double well and can tunnel from one side of the potential to the other, depending on the position of the oscillator. If the condensate is taken to be the environment for the oscillator, highly non-Markovian effects appear that can be observed in the non-exponential decay of the oscillator coherences [15,16]. In a recent experiment [17] it was shown that the spectral density of the environment in Quantum Brownian motion (see below) in an optomechanical resonator coupled to a heat bath, is highly non-Ohmic and produces non-Markovian dynamics in the resonator.…”
Section: Introductionmentioning
confidence: 99%